ASSESSMENT OF THE LOCALIZATION OF HYPOCENTERS OF CRUSTAL EARTHQUAKES RELATIVE TO THE DEPTH AND RELIEF OF THE BORDER DENSITY STRATIFICATION IN THE CRUST OF THE NORTHEASTERN SECTION OF THE REFERENCE GEOLOGICAL-GEOPHYSICAL PROFILE 3-DV - N. K. Gayday (Геодинамика и тектонофизика)
The total length of the seismic profiles in the northeastern regions ofRussiaand, accordingly, the area of the territories covered by the seismic data interpretations, remains insignificant in comparison with the total area of these regions. At the same time, the geological objects in the northeastern regions attract much attention in view of their prospects, including potential mineral resources. The challenge is to construct the regional models of the crust structure without deep seismic survey data, and to analyze the regional seismicity that depends on the features of the deep crust structure. We develop a density model of the crust structure using the new interpretational gravimetry method. The density modeling results show that the density changes in the crust can be used to estimate the position of a surface separating the lower (quasi-homogeneous) and upper (heterogeneous) parts of the crust, i.e. to assess the density boundary of stratification. This boundary is formed due to a complex of physical and chemical processes that facilitate the transition of the material in the lower part of the crust into the quasi-uniform (homogeneous) state. The study area is the junction zone of the Ayan-Yuryakh anticlinorium and Inyali-Debin synclinorium (62‒63°N, 148‒152° E). The initial interpretation of the deep seismic survey data on the reference geological-geophysical profile 3-DV was available, so the ambiguity of the density modeling was reduced. In turn, the density modeling results can provide additional information for geological-geophysical interpretation of the DSS results on the sites wherein the seismic profiles go along the fault zones. The relationship between seismic events and the relief of the density boundary of stratification in the crust was studied quantitatively on the basis of the data from the regional catalog of seismic events and the results of the earlier analysis of seismicity in the study area. The analysis shows that 74 % hypocenters are located above the density boundary of stratification. The earthquake hypocenters located at depths ranging from 20 to35 kmare usually confined to the systems of long-living regional crustal faults and occur below the density boundary of stratification. The energy class of such earthquakes does not exceed9. Inthe study area, the seismically active zones are mainly confined to the areas of subduction of the density boundary of stratification. Most of the earthquake epicenters (80 %) occur in the zones where the gradient of the relief change of the density boundary does not exceed 1. The number of recorded seismic events practically reduces to zero in the regions where the dip angle of the density boundary exceeds 65°.